MEMBANGUN PEMAHAMAN RELASIONAL MELALUI KOMUNIKASI INTERPERSONAL - Uus Uswatusolihah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
This paper focuses on how interpersonal communication is built to achieveagreement and uses phenomenological approach. It is based on a research on therelationship between lecturer and student in the process of thesis consultation inSTAIN Purwokerto.This paper explains that the model of their relationship is a role model, inwhich the role is formed through a surrounding structure. Form and context ofinterpersonal communication happen in a kind of face to face dialogues andindividually. The process of communication hardly found in groups, or withcommunication media such as telephone and internet. Seen from its effectiveness,it is found that most of the interpersonal communications are effective enough tobuild agreement between the individuals involved in the process.